The Influence of Entrepreneurship Education, Entrepreneurial Motivation, Income Expectations, Family Environment and the use of Social Media on Student Entrepreneurship Interest : Study on FEB students of Universitas PGRI Kanjuruhan Malang - Yuliya, Yuliya; Sulistyo, Sulistyo; Walipah, Walipah (IJBLE Scientific Publications Community Inc., 2025)
Entrepreneurship is a valuable profession as it plays an important role in achieving economic growth and reducing unemployment in a country. The aim of this study is to determine some of the effects of business education, business support, income requirements, family environment and social media usage on students' interest in business. The approach adopted in this study is a multi-faceted approach. There are 409 students in the Faculty of Business and Economics (FEB) of PGRI Kanjuruhan University Malang in the academic year 2021-2023. This sample was selected using the random sampling method with a sample size of 20% or 82 students. Data were collected through surveys distributed via Google Forms. The data analysis methods used included statistical and multivariate analysis with the help of SPSS version 26.0 application. The results showed that: (1) entrepreneurship education, entrepreneurship support, income expectations, family environment and social media use affect entrepreneurship; (2) business education affects business interests; (3) business support affects business performance; and (4) income expectations affect business preferences. (5) family environment affects entrepreneurial tendencies. (6) Social media use affects commercial interests